Development of Simple Sequence Repeat of Monochamus alternatus (Coleoptera: Cerambycidae) Based on Restriction Site-Associated DNA Sequencing - Jintao Lu; Senzhe Zhang; Jiaxin Liu; Yuhua Zhang; Lijuan Hu; Zhende Yang; Ping Hu (Biology)
Monochamus alternatus, a pest posing a serious threat to coniferous species, such as Pinus massoniana, has had devastating effects on pine forests due to its association with Bursaphelenchus xylophilus. The creation of unique simple sequence repeat (SSR) primers for M. alternatus is crucial, as there has been little study of the species’ phylogeography. The aim of this study was to identify and create polymorphic SSR primers by sequencing samples of M. alternatus obtained from three different sampling points using the restriction site-associated DNA sequencing (Red-seq) approach. Subsequently, supplementary samples were integrated, and genetic typing was performed utilizing the identified polymorphic primers. Through comprehensive analysis, a total of 95,612 SSR loci were identified. Among these, mononucleotide repeats (51.43%), dinucleotide repeats (28.79%), and trinucleotide repeats (16.74%) predominated among the SSR motif types. Ultimately, 18 pairs of SSR primers were screened out, demonstrating stable amplification and high polymorphism. Genetic typing revealed that the mean number of alleles (Na) for these primer pairs ranged from 3 to 8, observed heterozygosity (Ho) ranged from 0.133 to 0.733, polymorphic information content (PIC) ranged from 0.294 and 0.783, and Shannon’s index (I) ranged from 0.590 to 1.802. This study effectively produced 16 pairs of SSR primers that can be applied to different populations of M. alternatus. As a result, important tools for furthering studies on the phylogeography of pine wood nematodes, creating genetic maps, gene mapping, and carrying out in-depth investigations into gene function have been made available.